Ultimate presentations : master the art of giving fantastic presentations and wowing employers - Surti, Jay (Kogan Page, 2018)
"Does the thought of delivering a presentation fill you with dread? Do you want to learn how to give a fantastic presentation and impress an audience? Ultimate Presentations covers every aspect of this essential business skill: how to prepare, how to structure a great presentation, using technology and visual aids, communicating a strong message, tailoring your presentation to your audience, highlighting your personal skills through your presentation, time management and dealing with Q and As. Business presentation expert Jay Surti guides you through the most common obstructions to giving good presentations and how to overcome them, from nerves and uncomfortable body language, to voice tone and physical habits. Insightful guidance on coping with the unexpected, such as interruptions, technology breakdowns or difficult questions helps you to feel prepared and confident, no matter what happens during your presentation. The ability to deliver outstanding presentations is a lifelong skill that remains relevant throughout an entire career and can boost employability and progression."--Provided by publisher.